ILCA and ILRAD merge to form ILRI - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Ethiopia and Kenya have been asked to host jointly the new International Livestock Research Institute (ILRI). The two-country host status recognizes the continuing strong support being provided by the governments of Ethiopia and Kenya to livestock...